A Methyltransferase Inhibitor (Decitabine) Alleviates Intergenerational Effects of Paternal Neonatal Exposure to Anesthesia With Sevoflurane. (October 2020) - Xu, Ning; Lei, Lei; Lin, Yunan; Ju, Ling-Sha; Morey, Timothy E.; Gravenstein, Nikolaus; Yang, Jianjun; Martynyuk, Anatoly E.
Abstract : BACKGROUND: Neonatal exposure to sevoflurane induces neurobehavioral and neuroendocrine abnormalities in exposed male rats (generation F0) and neurobehavioral, but not neuroendocrine, abnormalities in their male, but not female, offspring (generation F1). These effects of sevoflurane are accompanied by a hypermethylated neuron-specific K + -2Cl − ( Kcc2 ) Cl − exporter gene in the F0 spermatozoa and the F1 male hypothalamus, while the gene's expression is reduced in the F0 and F1 hypothalamus. We investigated whether inhibition of deoxyribonucleic acid methyltransferases (DNMTs) before paternal sevoflurane exposure could alleviate the anesthetic's F0 and F1 effects. METHODS: Sprague-Dawley male rats were anesthetized with 2.1% sevoflurane for 5 hours on postnatal day (P) 5 and mated with control females on P90 to generate offspring. The nonselective DNMT inhibitor decitabine (0.5 mg/kg, intraperitoneally) was administered 30 minutes before sevoflurane exposure. The F0 and F1 male rats were evaluated in in vivo and in vitro tests in adulthood. RESULTS: Paternal exposure to sevoflurane induced impaired prepulse inhibition of the acoustic startle response and exacerbated corticosterone responses to stress in F0 males and impaired prepulse inhibition of the startle responses in F1 males. These effects were accompanied in both generations by reduced and increased expressions of hypothalamic Kcc2 and Dnmt3a/b, respectively. Decitabine deterred the effects of paternal exposure to sevoflurane in F0 and F1 males. CONCLUSIONS: These results suggest that similar decitabine-sensitive mechanisms regulating expression of multiple genes are involved in the mediation of neurobehavioral abnormalities in sires neonatally exposed to sevoflurane and in their future unexposed male offspring.